2017
DOI: 10.1111/1440-1681.12727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical lesion of basolateral amygdala nucleus on rat anxiety‐like behaviour under acute, sub‐chronic, and chronic stresses

Abstract: Stress contributes, as a risk factor, to such psychological disorders as anxiety. The effects of electrical lesions in the basolateral amygdala nucleus (BLA) were investigated on the locomotor activity and anxiety-like behaviour in different stress durations. For this purpose, rats were randomly allocated to control, sham, and experimental groups, the latter including groups with and without BLA nucleus subjected to acute, sub-chronic, and chronic stress conditions for 1, 7, and 21 days, respectively, applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The findings confirm the hypothesis that chronic stress is accompanied by a disturbance in STL as memory. It has been shown that chronic restraint stress impairs brain functions and memory processing in rats,[ 2 30 31 32 33 ] whereas it also alters such neuronal properties as suppression of neurogenesis in the dentate gyrus of the hippocampus[ 34 35 36 ] and changes the emotional and stress-related responses in animals. [ 2 30 ] Various mechanisms are involved in the stress responses; these include changes in stress biomarkers, hormones, and neurotransmitters as well as free radical generation and anti-oxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…The findings confirm the hypothesis that chronic stress is accompanied by a disturbance in STL as memory. It has been shown that chronic restraint stress impairs brain functions and memory processing in rats,[ 2 30 31 32 33 ] whereas it also alters such neuronal properties as suppression of neurogenesis in the dentate gyrus of the hippocampus[ 34 35 36 ] and changes the emotional and stress-related responses in animals. [ 2 30 ] Various mechanisms are involved in the stress responses; these include changes in stress biomarkers, hormones, and neurotransmitters as well as free radical generation and anti-oxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they proposed that there were more changes in subchronic restraint stress on BWD. [17] Collectively, the findings of the current and previous studies suggested that stress duration (even with different kinds of stress) is the main factor that affects the BWD. In addition, it is proposed that the subchronic stress corresponds to the alternation of food intake responses similar to acute stress and reduces food intake and body weight.…”
Section: Discussionmentioning
confidence: 65%
“…They demonstrated that subchronic stress (7 days) has the most deleterious emotional stress. [121617] In this regard, previous studies also have shown that acute stress is associated with the reduction of food intake,[439] while chronic stress increases the food consumption. [40] Moreover, it seems that changes of food intake are related to the stressor's characteristics such as type stress, duration of stress, the intensity of stress, and the individual's stress characteristics, metabolic state, and dietary in stress condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…consecutive days) and chronic (stress exposure for 21 consecutive days) stress in rodents which confirms that anxiety behaviour induced by chronic stress is in fact mediated by the BLA [217]. Besides this, Section 2.3.2 C also mentions various studies which elaborate on how molecules such as GAD, GR and BDNF in the BLA are essentially involved in mediating fear responses are affected by stress.…”
Section: Basolateral Amygdala: the Primary Mediator Of Fear And Anxiementioning
confidence: 62%